Policy tools for carnivore reintroduction: lessons learned from past wolf reintroductions in the western United States - Manzolillo, Brielle Rose, author; Schultz, Courtney, advisor; Teel, Tara, committee member; Cheng, Tony, committee member (Colorado State University. Libraries, 2021)
In November 2020, Colorado citizens passed a historic vote to reintroduce gray wolves to the state. Colorado Parks and Wildlife (CPW), the state wildlife agency, was tasked with creating management plans and policy. Wildlife managers and policy makers have the opportunity to consider different paths forward, drawing on the lessons of the past to lead to a successful wolf reintroduction program. Past reintroduction efforts in the western United States could provide valuable perspectives on the management and policy tools available to Colorado. In order to inform this process and use this opportunity to assess policy tools for addressing multi-jurisdictional conservation challenges like carnivore reintroduction, this thesis research had two primary objectives: analyze perspectives on policy tools utilized in past reintroductions, including the capacities needed for successful tool implementation; and synthesize specific suggestions and considerations for Colorado. In order to meet these objectives, I interviewed 42 individuals from state, federal and Tribal land and wildlife management agencies, and stakeholders from non-profit organizations and livestock associations. Interviewees were from past reintroduction areas of the Northern Rocky Mountains (i.e. Idaho, Montana, Wyoming) and the Southwest (i.e. New Mexico, Arizona), and Colorado. This thesis consists of four chapters: a brief introductory chapter, a second chapter that is a practitioner report of my findings, a third chapter that is an article intended for submission to a peer-reviewed journal, and a conclusion chapter. The practitioner report is a document aimed for practitioner and stakeholder audiences and provides a robust overview of findings on interviewee perspectives of a variety of management and policy strategies, along with specific recommendations for Colorado. The intent of this chapter is to provide Colorado wildlife managers and policy makers a detailed overview of our research and findings. My findings emphasize the need for collaborative processes and relationship building with stakeholders, and the flexibility to tailor strategies to local needs. The second stand-alone chapter, which will be submitted to a peer-reviewed journal, offers a policy design perspective on carnivore reintroduction. This chapter provides a narrower range of our findings in the context of policy design literature. Findings contribute to existing literature and emphasize the need for a mixed tool approach to management in order to address the diversity of targets and policy goals, address issues of scale, and leverage capacity. Overall, insight from this research could help to inform Colorado decision-makers on ways to move forward with planning for future wolf reintroduction. This research also contributes to the growing body of literature on using a policy design perspective to inform and analyze complex wildlife management and conservation issues. Further research is still needed to better evaluate overall effectiveness of policy tool choices and tailor specific reintroductions according to temporal and spatial scales. Future research should also be done to provide a robust stakeholder analysis for Colorado, as it is important to incorporate stakeholder perspectives into policy decisions.
Keywords: Colorado; policy design; wolves; human-wildlife conflict; carnivores; wolf reintroduction